Severe haematological toxicities in relapsed ovarian cancer treated with olaparib or niraparib: an Italian cost-minimization analysis. (May 2019) - Lazzaro, Carlo; Mazzanti, Nicola Amedeo; Parazzini, Fabio
The aim of this paper is to compare the cost for managing severe haematological toxicities (HTs: anaemia, neutropenia, thrombocytopenia) in patients with pretreated, relapsed BRCA -mutant positive (+) ovarian cancer (OC) receiving second-line therapy with olaparib or niraparib. As reported for treatment groups of randomized controlled trials, the incidence of anaemia, neutropenia and thrombocytopenia for olaparib (niraparib) was 0.071, 0.432 and 0.062 (0.253, 0.196 and 0.338), respectively. A one-year decision-tree cost-minimization analysis and a three-year budget impact analysis (BIA) were performed from the viewpoint of the Italian National Health Service (INHS). Health care resources funded by the INHS were identified and quantified based on the literature and expert opinion; they were costed via published sources and expressed in 2018 euro (€) amounts on a per-patient basis. One-way sensitivity analysis (OWSA) and scenario analysis tested the robustness of the base case findings. Our results show that the costs for managing anaemia, neutropenia and thrombocytopenia with olaparib (niraparib) are €440.63, €1032.76 and €171.01 (€1568.82, €468.90 and €936.06), respectively. The overall cost for HT management reaches €1644.41 and €2973.78 for olaparib and niraparib, respectively. Overall savings in favour of olaparib is €1329.37. BIA shows that olaparib can save the INHS €2.322m over a three-year timespan. Sensitivity analyses confirm the robustness of the baseline findings. Despite some limitations in our study, the results of the cost-minimization analysis show that olaparib is a safe and cost-saving health care programme for the INHS for the management of HTs in patients receiving second-line therapy for BRCA + OC.